2007
DOI: 10.1103/physrevlett.98.235002
|View full text |Cite
|
Sign up to set email alerts
|

Conical Forward THz Emission from Femtosecond-Laser-Beam Filamentation in Air

Abstract: We attribute a strong forward directed THz emission from femtosecond laser filaments in air to a transition-Cherenkov emission from the plasma space charge moving behind the ionization front at light velocity. Distant targets can be easily irradiated by this new source of THz radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
275
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(292 citation statements)
references
References 20 publications
(16 reference statements)
13
275
0
Order By: Relevance
“…This nonlinear propagation process has attracted many research interests. The reason is not only the rich physics involved, but also its various potential applications, such as remote sensing of atmospheric pollution [3], pulse compression down to few cycle regime [4], triggering and guiding of electric discharge [5], remote THz pulse generation [6], to name a few. In the last few years, the interaction of two filaments in gases and solids has triggered new research interests [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…This nonlinear propagation process has attracted many research interests. The reason is not only the rich physics involved, but also its various potential applications, such as remote sensing of atmospheric pollution [3], pulse compression down to few cycle regime [4], triggering and guiding of electric discharge [5], remote THz pulse generation [6], to name a few. In the last few years, the interaction of two filaments in gases and solids has triggered new research interests [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Conical forward THz emission from femosecond-laser-beam filamentation in air is also partially attributed to Cherenkov radiation by some authors [4]. For the case of simplicity, the motion of electrons is usually assumed uniform [5].…”
Section: Introductionmentioning
confidence: 99%
“…Filamentation deserves attention because it allows the generation of high-intensity THz radiation and management of its properties (intensity, polarization and radiation pattern) by varying the pump pulse duration and focusing conditions [12,13]. The physical origin of the THz radiation is attributed to the transition Cherenkov emission process [14,15]. One of the important properties of THz radiation is the polarization state.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important properties of THz radiation is the polarization state. Previously [14,16], it has been shown that the integrated field of the THz beam has a radial polarization. In the latest research, these results have been supplemented with the fact that the polarization of the THz field has an elliptic structure [17,18].…”
Section: Introductionmentioning
confidence: 99%